Building Credibility with Comprehensive Citation Practices - Pavithra Subramanian; Raghuraman Soundararajan; Jyotsna Makol (Indian Journal of Radiology and Imaging)
Honoring those who paved the way and paving the way for others is an old saying and practice that emphasizes the importance of acknowledging the contributions of others while also guiding and mentoring those who follow in your footsteps. In academic and scientific writings, citations are very important for maintaining the integrity, credibility, and progression of scientific knowledge. This article examines the significance of citations, their various types and methods, and the different styles used. By focusing on best practices and common errors, this article aims to guide researchers in effectively incorporating citations to enhance their work's visibility and impact. It analyses the different types of citations, including direct quotes, paraphrases, and summaries, and discusses the major citation systems such as the Vancouver and Harvard styles. The article also examines the common errors in citation practices and offers guidelines for accurate referencing. It also reviews various reference management software that facilitate to organize and automate the citation process. The impact of citations on bibliometric measures such as impact factor, H index, CiteScore, etc., which assess the influence and productivity of research, is also discussed. Further, the article briefly delves into the utility of artificial intelligence in citation management and future directions in citation practices. The goal of this article is to elevate the quality and credibility of academic publications in the area of medicine by focusing on the principles and methods of effective citation.